Implementing a pharmacist-led transition of care model for posttransplant hyperglycemia. (4th April 2021) - Do, Vincent; Haakinson, Danielle; Belfort-DeAguiar, Renata; Cohen, Elizabeth
Abstract: Purpose: The implementation of a pharmacist-managed transition of care program for kidney transplant recipients with posttransplant hyperglycemia (PTHG) is described. Methods: In September 2015, a collaborative practice agreement between pharmacists and transplant providers at an academic medical center for management of PTHG was developed. The goal of the pharmacist-run service was to reduce hospitalizations by providing care to patients in the acute phase of hyperglycemia while they transitioned back to their primary care provider or endocrinologist. For continuous quality improvement, preimplementation data were collected from August 2014 to August 2015 and compared to postimplementation data collected from August 2017 to August 2018. The primary endpoint was hospitalizations due to hyperglycemia within 90 days post transplantation. Secondary endpoints included emergency department (ED) visits due to hypoglycemia and the number of interventions performed, number of encounters completed, and number of ED visits or admissions for hypoglycemia. A Fisher's exact test was used to compare categorical data, and a Student t test was used to compare continuous data. A P value of <0.05 was considered to be statistically significant. Results: Forty-three patients in the preimplementation group were compared to 35 patients in the postimplementation group. There was a significant reduction in hospitalizations due to hyperglycemia in the postimplementation versus the preimplementation group (9 vs 1, P < 0.05); there was a reduction in ED visits due to hyperglycemia (5 vs 0, P = 0.06). There were no ED visits or hospitalizations due to hypoglycemia in either group. Clinical transplant pharmacists performed an average of 8.3 (SD, 4.4) encounters per patient per 90 days. Conclusion: A collaborative practice agreement was created and successfully implemented. A pharmacist-managed PTHG program could be incorporated into the standard care of kidney transplant recipients to help minimize rehospitalizations due to hyperglycemia.